Transcriptomics and metabolomics analyses provide insights into resistance genes of tree ferns - Yang, Weicheng; He, Qinqin; Zhang, Lijun; Xiao, Jiaxing; Yang, Jiao; Che, Bingjie; Zhang, BingChen; Chen, Handan; Li, Jiang; Jiang, Yu (Frontiers in Genetics, 2024)
As ancient organisms, tree ferns play a crucial role as an evolutionary bridge between lower and higher plant species, providing various utilitarian benefits. However, they face challenges such as overexploitation, climate change, adverse environmental conditions, and insect pests, resulting in conservation concerns. In this study, we provide an overview of metabolic and transcriptomic resources of leaves in two typical tree ferns, A. spinulosa and A. metteniana, and explore the resistance genes for the first time. The landscape of metabolome showed that the compound skimmin may hold medicinal significance. A total of 111 differentially accumulated metabolites (DAMs) were detected, with pathway enrichment analysis highlighting 14 significantly enriched pathways, including 2-oxocarboxylic acid metabolism possibly associated with environmental adaptations. A total of 14,639 differentially expressed genes (DEGs) were found, among which 606 were resistance (R) genes. We identified BAM1 as a significantly differentially expressed R gene, which is one of the core genes within the R gene interaction network. Both the maximum-likelihood phylogenetic tree and the PPI network revealed a close relationship between BAM1, FLS2, and TMK. Moreover, BAM1 showed a significant positive correlation with neochlorogenic acid and kaempferol-7-O-glucoside. These metabolites, known for their antioxidant and anti-inflammatory properties, likely play a crucial role in the defense response of tree ferns. This research provides valuable insights into the metabolic and transcriptomic differences between A. spinulosa and A. metteniana, enhancing our understanding of resistance genes in tree ferns.